2008
DOI: 10.1111/j.1600-0609.2008.01141.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of posaconazole vs. standard azole prophylaxis in high risk neutropenic patients in the Netherlands

Abstract: Given the underlying data and assumptions, the economic evaluation demonstrated that posaconazole prophylaxis is expected to be cost-effective compared with fluconazole/itraconazole in neutropenic AML/MDS patients after intensive chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 27 publications
1
55
0
1
Order By: Relevance
“…These findings correspond to evaluations with the generic model in other countries. Although there were differences in the evaluation and range of costs between these analyses, they all revealed that posaconazole prophylaxis can be considered a cost-effective strategy by preventing fungal infections [23,24,25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…These findings correspond to evaluations with the generic model in other countries. Although there were differences in the evaluation and range of costs between these analyses, they all revealed that posaconazole prophylaxis can be considered a cost-effective strategy by preventing fungal infections [23,24,25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…Based upon these results, Stam et al developed a predictive model of the average costs of the procedure and ascertained that prophylaxis with posaconazole appeared to be less expensive than with fluconazoleif the reduced incidence of IFI was taken into account. [47] With this in mind, our focus reverts to the other hospitalization costs since no difference was noted between the two groups in terms of prophylaxis cost. This appears to be directly related to the high cost of empirical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In all studies, utilizing posaconazole for the prophylaxis of IFIs decreased overall costs compared with fluconazole or itraconazole despite the higher medication acquisition cost. [43][44][45] While pharmacy costs tended to be much higher, the cost-avoidance came from decreasing IFIs and their extraordinarily high associated treatment costs.…”
Section: Pharmacoeconomic Analyses Of Prophylaxismentioning
confidence: 99%